Comparison of engineering and durability properties of fly ash blended cement concrete made in UK and Malaysia - N., Shafiq; M. F, Nuruddin; I, Kamaruddin (2007)
Annual global production of fly ash is similar to 6x10(8) ton out of which only 20 to 25% is utilised in the construction industry. Largely it is used as a partial replacement of cement for producing concrete. Properties of such concrete depend on the chemical composition of fly ash, source and method of burning of coal in power stations, etc. The present paper presents a comparative study on the properties on concrete containing fly ash obtained from two different sources, Drax Power Station, UK and Manjung Power Station, Malaysia. Fly ash obtained from Malaysia contained 11.47%CaO and its particles were coarser than the fly ash obtained from Drax, UK, which contained less calcium oxide (2.55%). Malaysian fly ash concrete required more water to achieve the targeted slump of 55 +/- 5 mm of fresh concrete, such concrete showed 4 to 7% high porosity and 27 to 36% low compressive strength as compared with the porosity and compressive strength of the concrete made with Drax, UK fly ash.